Language Is The Past, Present, And Future Of The Nation - Nasiba Jumaevna YARASHOVA (Genius Publishing Group, 2024)
It is the native language, the Uzbek language that shows the identity of the Uzbek people, its national integrity and makes them known to the world in itself, representing the spirit of the nation, the people. Our language is the property of our hearts, the great embodiment of our state. Preservation, development of language – this means the rise of the nation. The language represents the Past, Present, Future of the nation.
Keywords: Language; linguistics; national-cultural; anthropocentric